The Application of Eye-Tracking in Consumer Behaviour - Al-Azawi, Mohammad (International Journal of Engineering and Technology, 2019)
Eye tracking is one of the important technologies that is used to identify individual’s interest by recording and analysing his/her eyes’ movements. The attention and interest identification can be, then, used in various applications such as marketing and education. In this research, we utilise this technology and apply it in consumer behaviour application namely in retail items display and shelves organising. The gaze points data obtained from eye trackers is analysed and the consumer interest is discussed based on the analysis. From the analyses,it is shown that the human attention could be attracted by adding some irregularity in colour, shape, and size to the scene.